Ghana Access to Finance - World Bank Group (World Bank, Washington, DC, 2018)
Ghana has low levels of financial inclusion of individuals and access to finance for firms remains a major challenge; some of the key issues include low ownership and usage of accounts, dominance of cash, limited access points, limited electronic and mobile transactions, and high collateral, overall limiting outreach. Financial inclusion figures fare well compared to the Sub- Saharan Africa region, but in absolute terms only 40.5 percent of adults have an account at formal financial institution. Ownership and usage of electronic payment instruments is very low and the majority of transactions are conducted in cash. Mobile banking in Ghana is at a nascent stage with only 13 percent of adults having a mobile account and the number of mobile phone-based financial transactions is incipient. While majority of small and medium firms have access to formal accounts, large majority of them relies on internal finance for investments, with only around 23 percent having a bank loan or line of credit. Private sector credit to GDP is low at about 19 percent in 2014. Ghana’s limited infrastructure restricts access to both formal and unregulated financial institution, particularly in rural areas, with limited number of branches and ATM networks. Finally, high collateral requirements of over 200 percent of the loan amount for all-sized firms and over 250 percent for small firms, with real property as the most frequent type of collateral required, makes access to formal finance virtually prohibitive for many firms. The Access to Finance Note for Ghana identifies key issues and recommendations to enhance access to formal financial services for firms and to promote financial inclusion of individuals. The note provides a status of financial inclusion and access to finance in Ghana, along with a review of banking and microfinance sectors, including decomposition of interest rate spreads based on available data, leasing sector, as well as key financial infrastructure issues related to credit reporting, secured transactions, and payment system. Further, this note complements a collection of analytical work related to access to finance agenda, including notes on the microfinance sector, private equity and venture capital, diagnostic review of financial consumer protection, and a study on development finance, all providing more details on these topics.